Passive euthanasia and the right to die - Protopapadakis (Πρωτοπαπαδάκης), Evangelos D. (Ευάγγελος Δ.) (Bioethica, 2018)
The right to die is probably the most pivotal notion when it comes to the debate on euthanasia – provided, of course, that the issue of euthanasia is being discussed on a basis that concerns moral rights; on the emotional level it is definitely the most engaging and, hence, greatly influential. The right to die is often being challenged and, even, dismissed on grounds of being undocumented, unsound, and devoid of any actual meaning. In this short paper I will argue that the right to die in the case of passive euthanasia might find proper moral justification if it is considered as an autonomy-right.